Strive to be first or avoid being last: An experiment on relative performance incentives. - E. Glenn Dutcher; Loukas Balafoutas; Florian Lindner; Dmitry Ryvkin; Matthias Sutter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
Managers often use tournaments which motivate workers to compete for the top, compete to avoid the bottom, or both. In this paper we compare the effectiveness and efficiency of the corresponding incentive schemes. To do so, we utilize optimal contracts in a principal-agent setting, using a Lazear-Rosen type model that predicts equal effort and efficiency levels for the three mechanisms with the appropriate distribution of prizes. We test the model's predictions in a laboratory experiment and find that a mechanism which incorporates both competition for the top and away from the bottom produces the highest effort from agents, especially in contests of a relatively larger size. Avoiding being last is shown to produce the lowest variance of effort, be more effective and, in larger contests, more efficient than competing for the top. Finally, we show that behavior in all mechanisms is consistent with basic directional and reinforcement learning.
Keywords: M52; J33; J24; D24; C90; 330; tournament; reward; punishment; promotion; firing; contract; experiment; learning